The Role of Music Education on Students' Mental Health - Wang, Kun (International Journal of Social Sciences and Public Administration, 2024)
Music education, as an important form of education, has a positive effect on the development of students' mental health. By sorting out the basic theories of music education and students‘ mental health, this paper explores the mechanism of music education's influence on students’ mental health. Through empirical research, this paper finds that music education can effectively regulate students' emotions, improve social skills, promote cognitive development, and shape a sound personality. Meanwhile, this paper also further verifies the important role of music education in students' mental health through case studies. However, there are still some problems in current music education, such as the imperfection of the music education system and the insufficient construction of music teachers. Therefore, this paper puts forward countermeasure suggestions such as improving the music education system, strengthening the construction of music teachers‘ team, and focusing on the integration of music education and psychological education, with a view to improving the quality of music education and better playing its role in students’ mental health.